Theoretical Foundations of Internet Marketing in the Activities of Small Businesses (Eurasian Research Bulletin, 2023)
This article discusses the role of Internet marketing in the development of small businesses and the application of the theoretical foundations of electronic commerce. The article also reveals the prospects and benefits of e-commerce